Development of Pheromone-Based Mating Disruption for Three Lepidopteran Pests of Currant in Northern Europe - Anderbrant, Olle; Huynh, Hanh; Isaksson, Ann‐Kristin; Myhre, Line Beate Lersveen; Löfstedt, Christer; Mogan, Sigrid; Öberg, Elisabeth; Rantanen, Marja; Thöming, Gunda; Svensson, Glenn P. (Wiley-Blackwell, 2025)
Currant, and in particular blackcurrant, Ribes nigrum, is widely grown in Europe. It is the host of a number of pest insects, but their occurrence and the damage they cause vary geographically. In northern Europe, three lepidopteran species, the currant shoot borer (Lampronia capitella), the currant clearwing (Synanthedon tipuliformis), and the currant bud moth (Euhyponomeutoides albithoracellus), are particularly damaging and sometimes cause decreased plant vigour and drastic yield losses. With fewer insecticides approved for use and with an increased interest in organic production of currants, the need for alternative methods to control these moths is urgent. We here applied pheromone-based mating disruption in small and sometimes well isolated plantations in Finland, Norway and Sweden against the three pests using 15–25 g of active ingredients and 300 dispensers per ha. A strong trap shutdown effect, up to 100%, was recorded for the currant clearwing and the currant bud moth, but no effect on the most widespread species, the currant shoot borer, was noted. After 1 year of treatment, however, it was not possible to detect any significant effect on the damage level or on the future adult population size of the pests. We conclude that for the currant clearwing and the currant bud moth, mating disruption is likely to work with higher pheromone doses or modified dispenser density, whereas the reason behind the lack of effect on the currant shoot borer needs to be addressed by new experiments and observations of behaviour.
Keywords: Euhyponomeutoides albithoracellus; Lampronia capitella; pest management; Ribes; Synanthedon tipuliformis